Humble Leadership: Implications for Psychological Safety and Follower Engagement. Issue 2 (August 2016) - Walters, Kayla N.; Diab, Dalia L.
Abstract : Humility has emerged as a focus of leadership research in recent years, culminating with the theory of humble leadership. The current study added to the humble leadership literature by examining the relations among leader humility, psychological safety, and employee engagement. The study particularly examined the three constructs in the context of a mediational model. Data were collected from 140 workers who reported their perceptions of their immediate supervisor's humility, as well as their own psychological safety and work engagement. Results showed that the relation between humble leadership and employee engagement was fully mediated by psychological safety. Thus, by acknowledging limitations and mistakes, recognizing followers' strengths and contributions, and modeling teachability, leaders can create an environment in which followers can act without fear of negative ramifications and can fully engage in their work.